Coherent terahertz microscopy of modal field distributions in micro-resonators - Nikollao Sulollari; James Keeley; SaeJune Park; Pierluigi Rubino; Andrew D. Burnett; Lianhe Li; Mark C. Rosamond; Edmund H. Linfield; A. Giles Davies; John E. Cunningham; Paul Dean (APL Photonics, 2021)
Near-field microscopy techniques operating in the terahertz (THz) frequency band offer the tantalizing possibility of visualizing with nanometric resolution the localized THz fields supported by individual resonators, micro-structured surfaces, and metamaterials. Such capabilities promise to underpin the future development and characterization of a wide range of devices, including THz emitters, detectors, optoelectronic modulators, sensors, and novel optical components. In this work, we report scattering-type scanning near-field optical microscopy using a THz-frequency quantum cascade laser (QCL) to probe coherently the localized field supported by individual micro-resonator structures. Our technique demonstrates deep sub-wavelength mapping of the field distribution associated with in-plane resonator modes in plasmonic dipole antennas and split ring resonator structures. By exploiting electronic tuning of the QCL in conjunction with the coherent self-mixing effect in these lasers, we are able to resolve both the magnitude and the phase of the out-of-plane field. We, furthermore, show that the elliptically polarized state of the QCL field can be exploited for the simultaneous excitation and measurement of plasmonic resonances in these structures while suppressing the otherwise dominant signal arising from the local material permittivity.